Conductive filament structure in HfO2 resistive switching memory devices. (September 2015) - Privitera, S.; Bersuker, G.; Lombardo, S.; Bongiorno, C.; Gilmer, D.C.
Highlights: We study HfO2 based resistive switching memories in the low resistance state (LRS). STEM dark field and EELS are used to measure the size of conductive filaments. From electrical measurements metallic, ohmic behavior is observed in the LRS. Extracted resistivity from structural and electrical data is higher than pure Hf. We suggest strongly disordered, partially oxidized metallic Hf filament is formed. Abstract: We study the filament structure in 50 nm × 50 nm Resistive Random Access Memory (ReRAM) cells in the forming/set state with a Hf/HfO2 /TiN metal–insulator–metal stack by scanning transmission electron microscopy in cross section view. We reveal the filament morphology and, by the measurement of filament size and electrical resistance, evaluate the average resistivity of the filament material. The combination of the various data indicates the nanostructure of the conductive filament.